Research on Wi-Fi indoor positioning technology based on knowledge graph - Jiandong LI; Jingjing YANG; Ming HUANG (物联网学报)
Among the common Wi-Fi indoor positioning methods, most of the research focuses on the positioning accuracy, a little is on the application system to organize and process the existing indoor data efficiently in order to realize the indoor location service.To deal with these issues, the knowledge graph with the traditional indoor positioning technology was combined, and a practical positioning system was built with a variety of software development technologies.The system integrates the physical space and the information space.The information space includes indoor information acquisition, cloud services, information storage and computing parts.The physical space expresses the structure of the indoor space and data relationships.Finally, the WEBGL technology was used to display intuitive positioning and realize the visualization of indoor signal data and positioning results.The system has a complete data storage and use mechanism.After integrating the existing data information of the indoor internet of things equipment, it can provide users with room-level location services.The step-by-step positioning function of the system helps to reduce the time consumption of the system.